Standardization of the Electricity and Economic Potentials of Landfill gas (LFG) in Lagos, Nigeria. - Christopher N AKUJIEZE; Imoukhuede Moses IDEHAI (International Journal of Science and Engineering, 2014)
Globally, various practical data and scholarly estimations of the electricity potentials of landfill gas (LFG) have been forwarded and these can be juxtaposed for estimations in the megacity called Lagos. The calculated values were between 63.22- 700MW of  derivable electricity. However, in order to limit observable disparities and ambiguities in these derivations and thus allow for more accurate projections, these estimations can be gauged using as template; -stoichiometry, establishing 50% of landfill gas as methane, assuming 50% of this volume as recoverable, and using a proposed engine efficiency of 30%. This standardization projects a theoretical mean achievable electrical power of 121.69 MW for the Lagos area from a population of about 21 million with a generation per capita (GPC) of 0.63kg with biodegradable content of about 60%. The yearly electrical energy was placed at 1,066,004.4 MWh with tariff revenue in excess of US$ 106.6 million /yr. An accruing carbon credit of about US$75.59 million /yr is expected from certified emission reduction (CER). The projected derivations can be used as models for evaluation of the landfill gas and electricity potentials in many parts of the world.